Black devil and iron angel : the railway in nineteenth-century German realism - Youngman, Paul A. (Book collections on Project MUSE., 2005)
"In his emphasis on the legitimacy of both scientific and non-scientific approaches to understanding, Youngman follows the lead of Charles Percy Snow, who, in the mid-twentieth century, identified what he considered a dangerous rift between literary intellectuals on the one hand and scientists on the other. In order to prevent the establishment of two distinct cultures incapable of communicating with one another, he admonished intellectuals to establish a "third culture," a culture bridging the gap between the techno-scientific realm and the mytho-literary realm. Youngman's work is intended as a contribution to what has become known as Third-Culture Studies."--Jacket.